What can explain the Chinese patent explosion? - Eberhardt, Markus; Helmers, Christian; Yu, Zhihong (Oxford University Press, 2017)
We analyse the ‘explosion’ of patent filings by Chinese residents both domestically and in the United States during the early 2000s, employing a unique dataset of 374,000 firms matching patent applications to manufacturing census data. Our analysis reveals that patenting is highly concentrated among a small number of firms, operating in the information and communication technology sector. Although increases in patent filings by these companies are partly driven by increased R&D intensity, our analysis suggests that the explosion of patent filings at the Chinese patent office is driven by factors other than underlying innovative behavior, including government subsidies that encourage patent filings directly.